ADHESIVE PROPERTIES OF RESTORATIVE MATERIALS AND LONG-TERM DURABILITY ENHANCEMENT METHODS: A PRECLINICAL STUDY - I.Sadiqova.; A.Xasanov.; N.Madaminova.; Sh.Ruziev. (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
The longevity of dental restorations depends significantly on the durability of the adhesive interface between restorative materials and tooth tissues. This preclinical investigation examined the adhesive properties of contemporary restorative materials and evaluated various methods to enhance their long-term durability. Three composite resin systems (microhybrid, nanofilled, and bulk-fill) and two glass ionomer materials were tested using shear bond strength testing at baseline, three months, and six months. Specimens were exposed to thermocycling and stored in distilled water or acidic solutions to simulate clinical conditions. Results demonstrated that nanofilled composites exhibited superior initial bond strength (28.5 ± 2.3 MPa) compared to microhybrid (25.3 ± 1.9 MPa) and bulk-fill composites (22.1 ± 2.0 MPa). Moisture control during restoration placement significantly influenced bond durability, with specimens prepared using rubber dam isolation maintaining 85% of initial bond strength after six months, whereas those without adequate moisture control retained only 67%. Application of hydrophobic resin coating over the adhesive layer improved long-term durability by 18% and reduced nanoleakage . These findings suggest that material selection, combined with proper moisture management and protective coating techniques, substantially enhances the durability of restorative adhesive interfaces and clinical longevity of restorations.